1990
DOI: 10.1080/14640749008401246
|View full text |Cite
|
Sign up to set email alerts
|

Tests of Dual Process Theory: Word Priming and Recognition

Abstract: Dual process theory postulates two representational processes: Activation of a representation makes the mental event more easily and automatically accessible. Elaboration of a mental event produces access to the representation through search and retrieval processes. We explored word priming in recognition and in a stem completion task where the primed word was one of several possible completions for a 3-letter stem. The main hypothesis was that priming has similar and parallel effects in the two tasks. The ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(30 citation statements)
references
References 26 publications
0
29
1
Order By: Relevance
“…Second, in dual-retrieval theory (e.g., Brainerd et al, 2002), one of the most important aspects of verbatim traces is that these traces consist predominantly of surface (i.e., for visual word stimuli, letter and word forms) information. However, relational processing can promote elaborative processing (i.e., the process of relating semantic information from the stimulus event to semantic memory; Craik & Tulving, 1975) and it has been argued that elaborative processing can promote the integration of surface information (e.g., Mandler, Hamson, & Dorfman, 1990). In short, there are at least a couple of reasons to think that relational processing at study could increase the strength of verbatim traces and, as in the experiments here, lead to an advantage for related recall even during the direct access phase.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in dual-retrieval theory (e.g., Brainerd et al, 2002), one of the most important aspects of verbatim traces is that these traces consist predominantly of surface (i.e., for visual word stimuli, letter and word forms) information. However, relational processing can promote elaborative processing (i.e., the process of relating semantic information from the stimulus event to semantic memory; Craik & Tulving, 1975) and it has been argued that elaborative processing can promote the integration of surface information (e.g., Mandler, Hamson, & Dorfman, 1990). In short, there are at least a couple of reasons to think that relational processing at study could increase the strength of verbatim traces and, as in the experiments here, lead to an advantage for related recall even during the direct access phase.…”
Section: Discussionmentioning
confidence: 99%
“…Unstudied words that are orthographically similar to previously studied words have shown an advantage over orthographically dissimilar new words in single-stimulus perceptual identification tasks (e.g., Jacoby, 1983;Rueckl, 1990). Also, in word-stem completion, people are more likely to produce completions that rhyme with previously studied words than completions that are phonologically or orthographically unrelated to studied words (Mandler, Graf, & Kraft, 1986;Mandler, Hamson, & Dorfman, 1990). Priming also occurs in word fragment completion (though apparently not in perceptual identification) for both previously seen compound words (e.g., toothpaste, heartache) and for compound words consisting of recombined elements from studied items (e.g., toothache) (Reinitz & Demb, 1994).…”
Section: Methodsmentioning
confidence: 97%
“…when retention is based primarily on activation (Graf & Mandler, 1984;Graf et al, 1982). It has also been shown that recognition and priming (as exhibited in stem completions) respond in a similar fashion to manipulations of repetition (Graf & Mandler, 1984;Jacoby & Dallas, 1981) and type of activation (Mandler, Graf, & Kraft, 1986;Mandler, Hamson, & Dorfman, 1990) and exhibit parallel rates of forgetting in both normals (Graf & Mandler, 1984;Jacoby, 1983a) and amnesic patients .…”
mentioning
confidence: 93%